텅스텐이 첨가된 슈퍼 2상 스테인리스강의 내식성에 미치는 시효처리의 영향 - 김수천(Soo-Chun Kim); 최한글(Han-Gul Choi); 김윤규(Yun-Kyu Kim); 이종문(Jong-Mun Lee); 박진환(Jin-Hwan Park); 강창룡(Chang-Yong Kang) (Han-guk haeyang gonghak hoeji (Online), 2009)
The effect of aging on the precipitation of the $σ$ phase and the corrosion resistance in tungsten substituted super duplex stainless steels was investigated. The volume fraction of the $σ$ phase and the current density increased with aging at temperatures up to $750^{°}C$ and then decreased. With an increase in aging time, the volume fraction of the $σ$ phase and the current density also increased. The $σ$ phase hardly influenced the corrosion resistance. With the substitution of tungsten for molybdenum in super duplex stainless steel, the volume fraction of the $σ$ phase and the current density decreased remarkably.